Proposal of recreational activities in the community "La Sabana" - Osvaldo Matos-Leyva; Pedro Arrúe-Martínez (Universidad de Guantánamo, 2014)
This investigation responds to the need of increasing the power of the preparation of Recreation professors to achieve a community's greater incorporation to the sports recreational activities of the complex "La Sabana" of Puriales, for the complete satisfaction and the well-being in the physiological, mental and social order, and in that way create a culture of good use of free time. The creation of a system of activities intended to be recreational offers to the professors of physical recreation of this community the possibility of getting better participation of children, teens and young people´s population. As we used scientific methods of investigation we explored the theoretical, empiricist and mathematician levels.